CONTENT VALIDITY OF PHOSIK USING CVI METHOD - Nazatul Syima Mohd Nasir; Hutkemri Zulnaidi; Rohaida A. Rahmat; Siti Bahirah Saidi (Journal of Islamic, Social, Economics and Development, 2023)
This study aims to examine the content validity of PhoSIK for TESL pre-service teachers using the Content Validity Index (CVI). Seven experts were selected through sampling aimed at evaluating content consisting of three (3) professional university experts (in multimedia, digital, and psychometric learning) and three (3) subject experts from public education institutes. The instrument involves 73 items with three (3) main constructs. The results of the study show that the instrument has positive content validity and proves that PhoSIK has great potential to be promoted as a good instrument to measure the perception of pre-service TESL teachers towards essay writing in the future.